Production of methyl ethyl ketone from biomass using a hybrid biochemical/catalytic approach - Multer, Alisha; McGraw, Nathan; Hohn, Keith L.; Vadlani, Praveen V. (My University, 2013)
The recent demand for sustainable routes to fuels and chemicals has led to an increased amount of research in conversion of natural resources. A potential approach for conversion of biomass to fuels and chemicals is to combine biochemical and chemical processes. This research used microbial fermentation to produce 2,3-butanediol, which was then converted to methyl ethyl ketone by dehydration over a solid acid catalyst. The fermentation process was performed using the bacteria Klebsiella oxytoca (K.O). 2,3-butanediol then dehydrated to form methyl ethyl ketone on a solid acid catalyst, the proton form of ZSM-5, and heat. The goal was to determine the reaction kinetics of 2,3-butanediol dehydration over ZSM-5, and to demonstrate the hybrid biochemical/thermochemical approach for synthesizing chemicals from biomass. It was found that ZSM-5 produced methyl ethyl ketone with high selectivity (greater than 90%), and could convert fermentative 2,3-butanediol to methyl ethyl ketone. The reaction order of 2,3-butanediol dehydration was found to be slightly large than one, and an activation energy of 32.3 kJ/mol was measured.
Keywords: Methyl ethyl ketone; Biomass; Microbial fermentation; Sustainable fuel